Deviations : A Gayle Rubin Reader - Rubin, Gayle (Book collections on Project MUSE., 2011)
Gayle Rubin laid the foundation for queer theory as a graduate student at Michigan in the early '70s with the essay "The Traffic in Women," which was followed a decade later by an equally influential essay, "Thinking Sex." This volume collects her essays covering topics ranging from BDSM to feminist debates on pornography and sex to lesbian and gay history.